In vitro lethal activity of extract protein Bacillus thuringiensis against Nematodirus spathiger eggs and infective larvae (L3) - Ochoa Silvera, Adolfo Alfredo (2015)
A suspension containing the total protein extract of Bacillus thuringiensis of five strains (kurstaki HD-1, thompsoni HD-542, neoleonensis T-24-001, israeliensis HD-500 and israeliensis WHO-2013-9) was obtained. The concentration (mg/ml) of each strain was determined by the Biuret method. The nematicidal activity was evaluated in Petri plates facing eggs and infective larvae (L3) of Nematodirus spathiger against the suspension of total protein extract (1.2 ml). Five treatments (strains) and 10 repetitions were used. The control group contained only the nematodes. The Petri dishes were incubated at 25 °C for 24, 48 and 72 h. Kurstaki HD-1 strain in a concentration of 5.042 mg/ml showed the best anthelmintic efficiency in the three incubation times, obtaining 44.7% mortality in eggs and 45.6% in larva. The total protein extract of B. thuringiensis kurstaki HD-1 contains the nematicidal toxins that could be used for future in vivo experimentally infected animals with N. spathiger.